Economics of Accounting Performance Evaluation - Christensen, Peter Ove; Feltham, Gerald (Springer Series in Accounting Scholarship, 2005)
This is the second of two volumes in which the authors examine a variety of economic analyses of the decision-facilitating and decision-influencing roles of information that are pertinent to the study of the economic impact of accounting. The first volume focused on externally reported information in financial and product markets and did not model managers as economic agents - they were assumed to act in accordance with the instructions from the firm's owners. This second volume explicitly models managers' preferences and treats them as economic agents of the principal, who acts on behalf of the firm's owners. Accounting reports, and other contractible information, play key roles in motivating managers through incentive contracts. This volume provides an extensive examination of fundamental concepts in the economic analysis of incentives, with particular emphasis on the impact of the performance measurement system characteristics on the value of the firm. ECONOMICS OF ACCOUNTING: Volume II - Performance Evaluation is divided into four parts. Volume I contains Parts A through D, and the concepts developed in Part A are fundamental to both volumes. In Volume II, Part E initially focuses on optimal contracts in a single-agent /single-task/single-period setting, and explores how performance measure characteristics affect the principal's expected payoff. Multiple performance measures (including the stock price) and multiple tasks are introduced, thereby creating settings in which the principal is concerned with both the level of incentives and the congruency of the incentives with his own preferences. Part F considers the impact of start-of-period private management information (with communication to the principal) and limited commitment in single-period settings. These analyses serve as a bridge to the multi-period models explored in Part G. These multi-period models permit exploration of the impact of inter-period consumption preferences and limited inter-period commitments on preferences with respect to the inter-period correlation and timing of performance reports. Part H concludes the book with an analysis of multi-agent contracting in settings in which agents may coordinate their actions to their mutual benefit, and may even engage in overt collusion.